1999
DOI: 10.1897/1551-5028(1999)018<2512:alhatp>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Life-History Approach to Predicting the Recovery of Aquatic Invertebrate Populations After Exposure to Xenobiotic Chemicals

Abstract: Abstract-A combined empirical and theoretical study was conducted to evaluate the degree to which an understanding of the life histories of different freshwater invertebrate taxa could improve our ability to predict their relative rates of recovery after a toxic perturbation. Two chemicals, cypermethrin and 3,4-dichloroaniline, were introduced separately into large freshwater tanks (mesocosms, 1.25 m diameter, 1.25 m depth) containing established freshwater invertebrate communities. Immigration was simulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…This assumption is supported by the aforementioned microcosm experiment; indirect effects that originated from the reduction in population density of the sensitive competitor because of contamination increased insensitive Daphniidae abundance after contamination [17]. This is congruent with results from previous studies: in mesocosm communities, the recovery of aquatic invertebrate populations after pesticide exposure was reported to be faster for species with higher reproductive rates [30]. Furthermore, reproduction of Daphnia magna and other Daphnia species is density-dependently reduced under competition for common resources [29].…”
Section: Factors Affecting Population Recoverysupporting
confidence: 90%
“…This assumption is supported by the aforementioned microcosm experiment; indirect effects that originated from the reduction in population density of the sensitive competitor because of contamination increased insensitive Daphniidae abundance after contamination [17]. This is congruent with results from previous studies: in mesocosm communities, the recovery of aquatic invertebrate populations after pesticide exposure was reported to be faster for species with higher reproductive rates [30]. Furthermore, reproduction of Daphnia magna and other Daphnia species is density-dependently reduced under competition for common resources [29].…”
Section: Factors Affecting Population Recoverysupporting
confidence: 90%
“…The most sensitive endpoints for direct effects of the insecticides studied were structural ecosystem characteristics and usually concerned population densities of crustaceans and insects. These direct effects can generally be well predicted on the basis of laboratory tests with similar species as studied in the microcosm and mesocosm experiments (e.g., Crossland and Wolff, 1985;Fairchild et al, 1992a;Maund et al, 1998;Sheratt et al, 1999;Schroer et al, 2004). Different studies conducted with the same insecticide (e.g., chlorpyrifos, esfenvalerate, lambda-cyhalothrin) also yield similar critical threshold values (Tables 7 and 9).…”
Section: General Discussion and Conclusionmentioning
confidence: 76%
“…In general, recovery from pyrethroid exposure is likely to be a function of species-specific sensitivity and reproductive rates. For instance, Sherratt et al (1999) found that recovery times following cypermethrin exposures were longest for the most sensitive taxa and for those with low reproductive rates. Populations of flying, semi-aquatic insects began to re-establish within days of deltamethrin treatment, while abundances of aquatic invertebrates, such as cladocerans and fairy shrimp, were suppressed longer, as recovery was predicated on the number of resting eggs present in the pond environment (Lahr et al, 2000).…”
Section: Community Effects In High-tier Mesocosm Studiesmentioning
confidence: 99%